ANALISIS IMPLEMENTASI MANAJEMEN PELATIHAN KESIAPAN PETUGAS TANGGAP DARURAT DALAM MENGHADAPI BENCANA GEMPA BUMI PADA GEDUNG INSTALASI RAWAT INAP I (IRNA I) DI RSUP Dr. SARDJITO YOGYAKARTA - Fitri Rizki Adzhani; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Yogyakarta is prone to earthquakes. Therefore, every sector including hospitals has to be prepared to face earthquakes at anytime. RSUP Dr. Sardjito is the largest hospital in Yogyakarta and it has a system of emergency response. The hospital had a training and simulation program as a form of disaster preparedness. This study aimed to analyze the implementation of preparatory training to emergency response personnel in order to face the earthquake at the inpatient building I (IRNA I). This study was a descriptive qualitative study using in-depth interviews and observation sheet. The subjects of this study were five people as the key informants and one person as the informant triangulation. Analysis of the data performed data reduction, data presentation, and conclusion. The results showed in the planning management training had policies and commitments in the form of standard operating procedures (SOPs). The organizational structure in the implementation of the simulation training was a committee formed by the head of the installation. On the implementation of scheduling, training plan had been carried out by K3 unit. Before applying simulation, briefing was the first step which aimed to promote the scenario and the roles of each one. Promoting the procedure was also given to patients and the patient's family. During the promotion of the training, documenting by taking pictures was also held. The evaluation of the simulation was in the form of response time and video. Officers following the training in the ICCU was found quite active. Training department had a specific budget of education and training. However, IRNA I and ICCU building had no monitoring of the training and simulation for emergency response to the earthquake. Thus, hospitals should conduct monitoring to improve the quality of hospital services.